An Analysis of Stoic Characters from the Lies I Tell by Julie Clark - Absaraus Rajakumari A (Emerging Trends in Languages, 2026)
The research delves into the analysis of stoic characters from The Lies I Tell in various perspectives. The argument rests on those character's specific characteristics of being a stoic person and following the philosophies of the stoic human. Using a literary-philosophical approach, the analysis explores how both protagonists demonstrate the stoic ideal in distinct ways. Meg Williams, in her calculated acts of retribution, exhibits controlled reasoning and a deep, though unconventional, sense of justice. Kat Roberts, whose mission for truth is tempered by personal trauma, reveals inner strength, moral growth, and moderation. The paper closely examines several pivotal moments in the narrative that reflect stoic responses to adversity, emotional regulation, and ethical decision-making. It offers a contemporary canvas for the exploration and reinterpretation of stoic philosophy in modern literature. This study critically examines the embodiment of stoicism in the novel’s two central characters, Meg Williams and Kat Roberts, by analyzing their behaviors, choices, and inner conflicts through the lens of the four cardinal virtues of stoicism—prudence (wisdom), fortitude (courage), temperance (moderation), and justice. While the novel is primarily a story of deception and personal vendetta, it is equally a narrative about moral resilience, emotional discipline, and the pursuit of ethical balance in complex circumstances. Furthermore, this research addresses the broader significance of stoicism in contemporary fiction and how classical philosophical frameworks continue to shape the moral architecture of modern literary characters. By positioning the novel within the lineage of stoic literature, the study argues that stoic values not only endure in today’s storytelling but also evolve to reflect present-day complexities. Ultimately, the analysis affirms that Clark’s novel contributes meaningfully to philosophical literary discourse, offering readers a layered understanding of how ancient virtues remain relevant in interpreting character, choice, and justice in the modern world.
Keywords: Fortitude; Justice; prudence; stoic literature; stoic philosophy; stoicism; temperance